Studi Eksegesis Amsal 1-9: Suatu Antitesis Antara Orang Bebal dan Orang Bijak - Riski Riski; Farel Yosua Sualang; Endah Totok Budiyono (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2023)
The purpose of this research is to understand the meaning of fear of God in the text of Proverbs 1-9. Because the phrase "fear of God" often shows a gap in interpretation as an action-consequence relationship and re-interpretation in the orientation of obedience to wise qualities. This study uses a qualitative approach using the hermeneutic method of the wisdom genre, in particular paying attention coherently to the thematic phrase "fear of the Lord" in Proverbs 1-9. Thematic analysis of the relation of wisdom literature pays attention to translational or literal analysis, context, theological and especially the structure of antithetical parallelism, as well as the character-consequence pattern of the fool and the wise man. The result of this study is that the phrase "fear of God" describes a rebuke and rejection of wisdom which has bad consequences for a person. However, the peculiarity of wisdom in the phrase "fear of the Lord" provides a coherent orientation between knowledge and knowledge of God. It can be concluded that the basis of wisdom, namely "fearing the Lord" provides an understanding for wise and stupid people. The uniqueness of this interpretation is caused by the peculiarity of the pattern of words that are retribution (cause and effect) in the book of Proverbs 1-9. Not surprisingly, the meaning of the phrase "fear of God" emphasizes character/habits and the impact of true wisdom.